Hydroxyapatite nano-powders produced hydrothermally from nacreous material - OKTAR, FAİK NÜZHET (ELSEVIER SCI LTD, 2006)
Nano-powders of pure AB-type carbonated hydroxyapatite (HA) sized of similar to 100 nm were successfully produced via hydrothermal transformation (HT) of milled oyster shell powders at 200 degrees C. Low production cost, worldwide availability and natural-biological origin of raw materials are important features of the investigated process. When fine shell powders were used, the transformation reaction from aragonite to hydroxyapatite was accomplished within about 24 h. Calcite, concentrated at the outer surface of the shells, was less prone to transform into hydroxyapatite under the investigated hydrothermal conditions, even after prolonged reaction time (72 h) or in highly concentrated phosphate solutions. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: nacre; powders-chemical preparation; microstructure-final; apatite; biomedical applications; OSTEOBLASTS MAINTAINED INVITRO; OYSTER-SHELL; PINCTADA-MAXIMA; SOLUBLE MATRIX; BONE-FORMATION; IN-VIVO; CARBONATE; CALCIUM; CORAL; TEMPERATURE